The concept and the structure of the «intermediate zone» in the german word-building - Gruzdeva Natal'ia (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The following article is an overview of the German literature on the problem of the word-building components status in the German language. Initially these components were the free stems, which were attached to other stems in the act of compounding, but in the course of time they lost a part of their meaning. The article touches upon and systemizes the main conclusions of the works of M. Stepanova, W. Fleischer, L. Ortner etc., and discusses the following concepts: «intermediate zone», young affi x, semi-affi x, constituent with high frequency.